The Legislative Power of the House of Representatives after the Amendment to the 1945 Constitution of the Republic of Indonesia - Anis Musana (Constitutionale, 2020)
The legislative power after the amendment of the 1945 Constitution of the Republic of Indonesia (UUD 1945) resulted in a shift in legislative authority from the President to the House of Representatives (DPR). The legislative authority after the amendment of the 1945 Constitution predominantly rests with the DPR, however, the President and the Regional Representatives Council are also given the authority to form laws. The powers that be in the DPR do not necessarily make the DPR superior to the President and DPD in terms of legislation. It turns out that the strengthening of the legislative power that is in the DPR as a legislative body cannot prove that the resulting regulations are commensurate with the increased authority obtained after the amendments to the 1945 Constitution. In fact, regulations originating from the President and DPD as executive bodies appear to be more active than those that originate. from the DPR. This study aims to thoroughly analyze and map the legislative power of the DPR as well as the legislative power possessed by the President and DPD because after the amendment the three state institutions have legislative powers, if this happens it will have the potential to reduce the legislative power possessed by the DPR. The type of research used is a type of normative research with a Normative-Analytical approach that uses secondary data sources with primary, secondary, and tertiary legal materials.